Implikasi Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 Terhadap Kedudukan Anak Di Luar Perkawinan - Setyawan, Rahmad; Nur Sholikin; Al - Robin (Ahwaluna | Jurnal Hukum Keluarga Islam, 2024)
Abstract This research aims to explain and analyze the legal considerations and concurring opinion presented by Judge Maria Farida Indrati, as well as the implications of Constitutional Court Decision Number 46/PUU-VIII/2010 on the status of children born out of wedlock. This study is a library research using a descriptive-analytical method. The data in this research was obtained by examining Decision Number 46/PUU-VIII/2010, as well as various library references related to the issue under investigation. The research results show that the Constitutional Court has made a progressive and responsive legal breakthrough to achieve justice for children born out of wedlock, although within the legal considerations, a concurring opinion was expressed by Judge Maria Farida Indrati. This legal breakthrough declares that a child born out of wedlock (sirri) has a civil relationship with their mother and the mother's family, as well as with the man as the father, which can be proven based on science and technology and/or other legal evidence indicating a blood relationship, including civil relations with the father's family. The civil rights granted to a child born out of wedlock (sirri) do not conflict with the provisions concerning lineage, inheritance, and guardianship. A child born out of wedlock (sirri) can claim rights that are not regulated in fiqh, such as the right to education expenses, healthcare, living necessities, and future preparation. Additionally, the child can claim compensation for unlawful acts that harm others, as stipulated in Article 1365 of the Civil Code, or claim for breach of contract. In short, a child born out of wedlock (sirri) has civil rights unrelated to lineage, inheritance, guardianship, or any civil rights not related to the principles of munakahat according to fiqh. Keywords: The Status of Children Born Out of Wedlock; Marriage Registration; Constitutional Court Decision Number 46/PUU-VIII/2010.